Surface chemistry of biological apatites in mineralized tissues (on the example of spongy bone tissue). - Husak, E. V.; Danylchenko, S. M.; Gordienko, O. V.; Inshyna, N. M.; Oleshko, O. M.; Pogorielov, M. V. (Морфологія / Morphologia / Morfologìâ, 2016)
Background. It is well known that poorly crystallized carbonate apatite is the main mineral component of the normal calcified hard tissues of human skeleton. However, some attributes and characteristics of bioapatites in physiologically mineralized tissue remain undefined. It is thought that structural imperfections and surface properties of the bioapatite nanocrystals govern the crystal chemistry and therefore should be crucial factors in formation, resorption and remodeling behavior of the biominerals. The biocrystal surface plays an exceptional role as a boundary between mineral and organic components and location of the main processes. The correlations between structural defects and content of labile ions on the crystal surface may reflect some ultrastructural features of bioapatite and ability to ion exchange. Objective. The aim of the research was to study the crystal-chemical characteristics of bio-related calcium apatites. Methods. In our research we used pyrolysis and subsequent ultrasonication in aqueous medium. Because apatite solubility is minor at normal conditions, the free ions can be removed in aqueous solution, keeping unaffected apatite structure, and then their concentration can be determined by atomic spectroscopy (AS). Results. 60-70 % of Mg present in bone seems to be incorporated in bioapatite structure substituting Ca, while the remaining Mg is located on the bone mineral crystal surface where it is easily available and could be removed by ultrasonic treatment. Also we got evidence that Mg and Na in bone apatite can be both in structurally bounded (substituting calcium in lattice) and in labile state (localizing on the crystal surface), while K is not able to join the apatite structure in significant amount or to be chemically bounded to it.